Can clinical tests help monitor human papillomavirus vaccine impact?. Issue 5 (13th March 2013) - Meites, Elissa; Lin, Carol; Unger, Elizabeth R.; Steinau, Martin; Patel, Sonya; Markowitz, Lauri E.; Hariri, Susan
<x xml:space="preserve">Abstract</x> As immunization programs for human papillomavirus (HPV) are implemented more widely around the world, interest is increasing in measuring their impact. One early measurable impact of HPV vaccine is on the prevalence of specific HPV types in a population. In low‐resource settings, a potentially attractive strategy would be to monitor HPV prevalence using clinical cervical cancer screening test results to triage specimens for HPV typing. We assessed this approach in a nationally representative population of U.S. females aged 14–59 years. Using self‐collected cervico‐vaginal swab specimens from 4, 150 women participating in the National Health and Nutrition Examination Survey during 2003–2006, we evaluated type‐specific HPV prevalence detected by the Roche linear array (LA) research test on all specimens, compared with type‐specific HPV prevalence detected by LA conducted only on specimens positive by the digene hybrid capture 2 (HC‐2) clinical test. We calculated weighted prevalence estimates and their 95% confidence intervals (CIs), and examined relative type‐specific HPV prevalence according to the two testing approaches. The population prevalence of oncogenic HPV vaccine types 16/18 was 6.2% (CI:5.4–7.1) by LA if all specimens were tested, and 2.4% (CI:1.9–3.0) if restricted to positive HC‐2. Relative prevalence of individual HPV types was similar for both approaches. Compared with typing all specimens, a triage approach would require testing fewer specimens, but a greater reduction in HPV prevalence or a larger group of specimens would be needed to detect vaccine impact. Further investigation is warranted to inform type‐specific HPV monitoring approaches around the world.